2018
DOI: 10.3390/en11040806
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of Pre-Treatment Process Parameters to Generate Biodiesel from Microalga

Abstract: Cell disruption is an integral part of microalga production process, which improves the release of intracellular products that are essential for biofuel production. In this work, pre-treatment parameters that will enhance the efficiency of lipid production using high-pressure homogenizer on microalgae biomass will be investigated. The high-pressure homogenizer that is considered is a GYB40-10S/GY60-6S; with a pre-treatment pressure of 1000 psi, 2000 psi, and 3000 psi, the number of passes; 1, 2, and 3, a react… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 70 publications
0
9
0
Order By: Relevance
“…Response Surface Methodology (RSM) with Box-Behnken experimental design have been effectively applied to determined optimum conditions. Mathematical and statistical methods have been used to predict the effect of input process parameters based on the output responses [32][33][34]. The three parameters that most influence biodiesel production are: methanol/oil ratio, catalyst loading, and reaction time [35,36].…”
Section: Introductionmentioning
confidence: 99%
“…Response Surface Methodology (RSM) with Box-Behnken experimental design have been effectively applied to determined optimum conditions. Mathematical and statistical methods have been used to predict the effect of input process parameters based on the output responses [32][33][34]. The three parameters that most influence biodiesel production are: methanol/oil ratio, catalyst loading, and reaction time [35,36].…”
Section: Introductionmentioning
confidence: 99%
“…The impingment stress was reported as being proportional to the operating relative pressure in some types of homogenisers (Chisti and Moo-Young, 1986). As pressure drop is one of the main cell-breaking mechanisms, the system operating pressure is critical for process performance (Balduyck et al, 2018;Halim et al, 2012;Onumaegbu et al, 2018;Samarasinghe et al, 2012). Increasing the pressure in the HPH of Chlorella sp.…”
Section: High-pressure Homogenization (Hph)mentioning
confidence: 99%
“…Microbial fuel cell (MFC) is an attractive technology for sustainable development [1,2] that could be applied to wastewater treatment with bioelectricity generation [3,4]. Photosynthetic microalgae microbial fuel cell (MFC) could produce microbial lipid (could be converted to biodiesel [5]) and algal biomass besides electricity, while reducing greenhouse gas CO 2 by photosynthesis [6,7]. Many studies have demonstrated that the bioelectricity generation was correlated with oxygen availability in the cathode as O 2 is the electron acceptor [8][9][10].…”
Section: Introductionmentioning
confidence: 99%